2009
DOI: 10.17221/929-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Changes of Vegetable Oils during Microwave Heating

Abstract: Abstract:Oxidation changes of different types of vegetable oils were studied during microwave heating. Samples of vegetable oils (rapeseed, sunflower, soybean and corn oil), commercially available at the market in the Czech Republic, were heated in a microwave oven. Parameters as peroxide value, conjugated dienes and trienes levels were determined in oil samples before and after heating in the period from 3 to 30 minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 7 publications
3
21
0
Order By: Relevance
“…Thus, corn oil reached the peroxide value 10 mmol 0.5 O 2 kg −1 after 8‐min heating, while sunflower oil reached the same number 2 min earlier. In concord with other authors we found that microwave heating of corn oil for periods of 6, 8, and 10 min led to 3‐, 5‐ and 8‐times increase in its peroxide value, respectively, compared to that in fresh oil. The rise in conjugated dienes content in heated corn oil was very similar, too.…”
Section: Resultssupporting
confidence: 88%
“…Thus, corn oil reached the peroxide value 10 mmol 0.5 O 2 kg −1 after 8‐min heating, while sunflower oil reached the same number 2 min earlier. In concord with other authors we found that microwave heating of corn oil for periods of 6, 8, and 10 min led to 3‐, 5‐ and 8‐times increase in its peroxide value, respectively, compared to that in fresh oil. The rise in conjugated dienes content in heated corn oil was very similar, too.…”
Section: Resultssupporting
confidence: 88%
“…The values of CD and CT of BKSO increased significantly (p < 0.05) over time ( Table 2) but only a small difference was found in the CD and CT of MKSO stored at 65 °C. CD was produced at a higher level than the CT, which corresponded with results reported by Lukešová et al [28]. Increased CD and CT are associated with oxygen uptake and formation of peroxides during the early stages of oxidation as well as with the degradation of polyunsaturated fatty acids [27].…”
Section: Evaluation Of Oxidative Stabilitysupporting
confidence: 89%
“…There was no significant difference between heating methods although the K270 values for each sample significantly changed during heating (data not shown). Lukesova et al, (2009) reported that the PV, K232 and K270 in rapeseed, corn, soybean and sunflower oils increased due to microwave heating. They also noted that K232 were formed at higher levels compared to K270.…”
Section: Conjugated Dienes (K232) and Trienes (K270)mentioning
confidence: 99%
“…They also noted that K232 were formed at higher levels compared to K270. Vieira and Regitano-D'arce (1998) and Lukesova et al, (2009) noted that K232 was a good index for measuring oil deterioration after microwave heating.…”
Section: Conjugated Dienes (K232) and Trienes (K270)mentioning
confidence: 99%